2013
DOI: 10.1186/1471-2407-13-579
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the lifelong health impact and financial burdens of different types of lung cancer

Abstract: BackgroundOwing to the high mortality and rapidly growing costs related to lung cancer, it is worth examining the health benefits of prevention for major types of lung cancer. This study attempts to quantify the quality-adjusted life expectancy (QALE), loss-of-QALE, and lifetime healthcare expenditures of patients with different pathological types of lung cancer.MethodsA national cohort consisting of 66,535 patients with pathologically verified lung cancer was followed for 13 years (1998–2010) to obtain the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…By using a semiparametric method explained in detail in our previous article [13], we extrapolated the survival to lifetime to estimate the life expectancy of patients receiving one of three first-line treatments. The extrapolation method has been shown to be effective via computer simulations [14], mathematical proof [15] and corroboration by examples of lung cancer cohorts [13,16,17]. The iSQoL statistical package (www.stat.sinica.…”
Section: Effectivenessmentioning
confidence: 92%
“…By using a semiparametric method explained in detail in our previous article [13], we extrapolated the survival to lifetime to estimate the life expectancy of patients receiving one of three first-line treatments. The extrapolation method has been shown to be effective via computer simulations [14], mathematical proof [15] and corroboration by examples of lung cancer cohorts [13,16,17]. The iSQoL statistical package (www.stat.sinica.…”
Section: Effectivenessmentioning
confidence: 92%
“…We searched PubMed in January 2014 using the following keywords, as modified from our previous studies, to realize which cost issue(s) of SCLC had been reported in the literature: ([small cell lung cancer] NOT [non‐small cell lung]) AND ([“costs and cost analysis”{MeSH}] OR costs[Title/Abstract] OR cost effective*[Title/Abstract]) OR (cost*[Title/Abstract] OR “costs and cost analysis”[MeSH:noexp] OR cost benefit analysis*[Title/Abstract] OR cost‐benefit analysis[MeSH] OR health care costs MeSH: noexp) . We found that various issues, including work‐up modality, chemotherapy intensity, prophylactic cranial irradiation, granulocyte colony‐stimulating factor, prophylactic antibiotics, second line treatment, new drugs, and overall cost, had been reported since 2000 . However, the cost‐effectiveness of C‐TRT in LS‐SCLC had never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We searched PubMed in January 2014 using the following keywords, as modified from our previous studies, to realize which cost issue(s) of SCLC had been reported in the literature: ( 35 We found that various issues, including work-up modality, chemotherapy intensity, prophylactic cranial irradiation, granulocyte colony-stimulating factor, prophylactic antibiotics, second line treatment, new drugs, and overall cost, had been reported since 2000. [36][37][38][39][40][41][42][43][44][45][46][47] However, the costeffectiveness of C-TRT in LS-SCLC had never been reported. Our result did, however, reflect similar results in the literature that C-TRT versus C/T is associated with improved overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Although estimates of standardized mortality rates can still provide useful information on the impacts of diseases or technologies, which can then aid health policy decision, such comparisons for different illnesses have become less efficient, especially because for most cancers patients usually survive for more than 5-10 years, and thus one must wait for a long period of time for mortality to occur [1][2][3][4][5][6]. The current coding of one underlying cause of death might also underestimate the impact of other causes, including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the authors of this study have developed estimates of the expected years of life lost and loss-of-QALE that quantify the consequences of illness with life-year and QALY, respectively, which make possible direct comparisons of prevention with clinical care [1][2][3][4]15] if incidence rates can also be incorporated together [16]. It may thus be possible to quantify both incidence rates and how much utility is lost from developing a specific illness, rather than simply making policy decisions based on mortality rates.…”
Section: Introductionmentioning
confidence: 99%